Perceived usefulness of Artificial Intelligence on Public Relations Practices in Malaysia: A Pilot Study - Dzul Affandi Mat Noor; Ahlam Abdul Aziz; Shazleen Mohamed (LSPR Institute of Communication & Business, 2025)
This pilot study investigates the perceived usefulness of Artificial Intelligence (AI) in Public Relations (PR) practices from the perspective of Malaysian practitioners. With the increasing adoption of AI across industries, PR professionals are beginning to explore how such technologies can enhance strategic communication, media monitoring, campaign planning and stakeholder engagement. However, there is limited empirical research capturing these perceptions in the Malaysian context. Guided by the Technology Acceptance Model (TAM), this study aims to assess the extent to which AI is perceived to enhance efficiency, transform roles and support the core functions of PR. This study evaluates how practitioners view AI’s ability to streamline content creation, automate repetitive tasks and analyse media trends. Using a quantitative survey approach, data were collected from various Malaysian PR practitioners through an online questionnaire. Descriptive statistical analysis was employed to identify key patterns in perception. The results reveal that AI is generally perceived as a valuable tool for automating routine tasks such as press release writing, social media monitoring and media analysis. However, its perceived usefulness diminishes in areas requiring emotional intelligence, strategic judgment, or interpersonal engagement, such as crisis communication and relationship-building with stakeholders. The findings underscore a dual perception of AI as both an enhancer of efficiency and a potential disruptor of core human-centred PR functions. This study contributes to the growing body of knowledge on AI in communication by providing initial empirical insights from Malaysia, a region underrepresented in current discourse. It also lays the groundwork for future studies exploring behavioural intention and actual AI usage in PR, which could be investigated further. The study concludes by recommending skill development initiatives, ethical AI integration and policy support to ensure AI adoption aligns with professional standards and societal values.